Effective and Timely Evaluation of Pulmonary Congestion: Qualitative Comparison Between Lung Ultrasound and Thoracic Bioelectrical Impedance in Maintenance Hemodialysis Patients. Issue 6 (February 2015) - Donadio, Carlo; Bozzoli, Laura; Colombini, Elisa; Pisanu, Giovanna; Ricchiuti, Guido; Picano, Eugenio; Gargani, Luna
Abstract : Abstract: The assessment of pulmonary congestion in maintenance hemodialysis (MHD) patients is challenging. Bioelectrical impedance analysis (BIA) can estimate body water compartments. Natriuretic peptides are markers of hemodynamic stress, neurohormonal activation and extracellular volume overload. Lung ultrasound (LUS) has been proposed for the non-invasive estimation of extravascular lung water through B-lines assessment. Up to now, no study evaluated the correlation between B-lines, segmental thoracic BIA, and natriuretic peptides in MHD patients. The aims of this study were: (1) To validate LUS as a tool for an effective and timely evaluation of pulmonary congestion in MHD patients, in comparison with segmental thoracic BIA, and with natriuretic peptides; (2) To compare a comprehensive whole chest ultrasound scanning with a simplified and timely scanning scheme limited to the lateral chest regions. Thirty-one MHD adult patients were examined. LUS, total body and thoracic BIA, and natriuretic peptides were performed immediately before and after a mid-week dialysis session. The number of B-lines assessed by LUS was compared with total body and thoracic impedance data and with natriuretic peptides. Pre-HD B-lines ranged 0–147 (mean 31) and decreased significantly post-HD (mean 16, P < 0.001). A significant correlation was found between the number of B-lines and extra-cellular water index (ECWI, r = 0.45, P < 0.001), with thoracic impedance ( r = 0.30, P < 0.05), and with BNP ( r = 0.57, P < 0.01). The dynamic changes in B-lines correlated better with thoracic impedance than with total body impedance, and correlated with extra-cellular but not with intra-cellular water index. The correlation between B-lines and ECWI was similar when LUS was limited to the lateral chest regions or performed on the whole chest. Multivariate analysis showed that only segmental thoracic impedance was an independent predictor of residual pulmonary congestion. The dynamic changes in B-lines after hemodialysis are correlated to the changes in total body and extra-cellular water, and particularly to lung fluids removal. B-line assessment in MHD patients is highly feasible with a simplified and timely scanning scheme limited to the lateral chest regions. These premises make B-lines a promising biomarker for a bedside assessment of pulmonary congestion in MHD patients.